2018
DOI: 10.1515/hsz-2018-0203
|View full text |Cite
|
Sign up to set email alerts
|

Total yield of reactive species originating from an atmospheric pressure plasma jet in real time

Abstract: It is now well established that plasma-induced reactive species are key agents involved in many biochemical reactions. This work reports on the formation of plasma reactive species in an acidified ferrous sulfate (Fricke) solution interacting with an atmospheric pressure plasma jet (APPJ). A yield of ferric (Fe3+) ions measured using in situ absorption spectroscopy was attributed to the formation of plasma reactive species provided and/or originated in the solution. The results indicated that the number of rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Generally, in radiation research, the dose-rate effect is associated with the yield of specific reactive species, which induce chemical alterations in the biomolecular target 13 . Using a traditional chemical dosimeter in our previous study, we observed an increase in the total amount of reactive species as a function of frequency and voltage for the same LTP source 15 . Thus, the increase in the estimated dose rate with a frequency and voltage in this study can be related to the increase in the number and/or type of plasma species responsible for DNA damage.…”
Section: Resultsmentioning
confidence: 71%
“…Generally, in radiation research, the dose-rate effect is associated with the yield of specific reactive species, which induce chemical alterations in the biomolecular target 13 . Using a traditional chemical dosimeter in our previous study, we observed an increase in the total amount of reactive species as a function of frequency and voltage for the same LTP source 15 . Thus, the increase in the estimated dose rate with a frequency and voltage in this study can be related to the increase in the number and/or type of plasma species responsible for DNA damage.…”
Section: Resultsmentioning
confidence: 71%
“…2015; Adhikari et al . 2019) while measuring intermediate and short‐lived reactive species is neglected most of the time (Adhikari et al . 2019).…”
Section: Resultsmentioning
confidence: 99%
“…2019) while measuring intermediate and short‐lived reactive species is neglected most of the time (Adhikari et al . 2019). Thus, other mechanisms may be involved in the antimicrobial activity of plasma against natural flora compared to inoculated pathogenic microorganisms such as S. enterica .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…where p is the ambient pressure, δp is the pressure change, 63 T is the steady-state temperature, δT is the tempera-64 ture change and γ is the heat capacity ratio for helium 65 (1.66 at 293 K). Using ambient pressure of one atmosphere 66 (101 kPa) and a steady state temperature of 433 K, a tem-67 perature change of 0.8 K corresponds to a pressure change 68 of ±469 Pa. An SPL can be calculated from It is relevant to note that in our previous studies on the 33 biological effects of APPJ on biomolecular targets, which 34 were performed using the same plasma source and the 35 same electrical conditions, we observed damage to DNA 36 [32,33]. Thus, it indicates that the source that can be oper-37 ated at the safety sound level is capable of producing the 38 plasma components that can induce alternation to the cellular components.…”
mentioning
confidence: 99%